Examinations Pemeriksaan Ante-Mortem dan Post-Mortem Hewan Kurban di Paguyuban Kondang, Kota Kupang, Nusa Tenggara Timur: Ante-Mortem and Post-Mortem Examination of Sacrificial Animals at the Kondang Association, Kupang City, East Nusa Tenggara - I Gede Semarabawa (Cv. Utility Project Solution, 2023)
Inspection ante-mortem and post-mortem for sacrificial animals in the Kondang Association, The City of Kupang works to prevent the slaughter of animals that clearly show clinical symptoms of zoonotic diseases and to provide assurance that the carcass, meat and internal organs produced are safe and suitable for consumption. Inspection ante-mortem and post-mortem this is done by inspection, palpation and incision. Examination was carried out on 5 cattle and 3 goat. The inspection begin with checking the general condition of the livestock to see male/female sex, sterile/not, livestock temperature, and appetite. Inspection is carried out on the animal's attitude, general condition, movement, circumference of the horns and teeth. Inspection, palpation and incision are carried out on the head, carcass and internal organs such as the lungs, liver, spleen, heart and kidneys. During the ante-mortem and post-mortem examinations, no abnormalities or signs of zoonotic infectious diseases were found either in the carcasses or internal organs of all slaughtered animals. The decision was taken in accordance with the results of a series of checks that had been carried out that all carcass, meat and internal organs of all sacrificial animals slaughtered at the Kondang Association, Kupang City are good for human consumption.